Labour-based Construction Technology for Sustainable Rural Development Infrastructure - Shrestha, Diwat Kumar (Journal of Advanced Academic Research, 2017)
Labour-based construction technology is the most important aspect for the development of sustainable rural infrastructure. This study emphasizes on promoting this technology for the overall development and analyzes this aspect in the perspective of rural road bridge sector of Nepal. This technology relates to the environmental, socioeconomic, ownership, livelihood and sustainability aspects of the project area. Infrastructure development is very easy, but sustainability is the key issue which has to be addressed by the infrastructure projects. Labour-based infrastructure is one of the major components to achieve sustainability. Many sub-components to ensure labour-based aspects are identified and tested in this study.